iAgree: mobile application for english learning / Natasha Nuralanis Zulkipli and Azlina Bujang - Zulkipli, Natasha Nuralanis; Bujang, Azlina (2020)
Young children are often more attracted to use mobile learning applications because mobile learning applications are usually engaging, friendly and interactive. iAgree is an attractive mobile learning application to learn English which can be used offline in remote areas, where internet access is very limited or scarce. The uniqueness of iAgree where it can be used offline while its content reflects on pupils' local cultures and daily life activities will be the novelty of this application. The simplicity yet bold and bright color scheme selections of this application would be great features in order to grasp students' attention to easily use this application. Furthermore, as an alternative choice in order to cater the needs of rural students without internet access or having a very poor internet connection, both iAgree content and its progress tracking feature will work even on offline mode due to its ability to stand alone. iAgree will ensure that rural students will not be left far behind their counterparts in urban areas, whose internet connections are much better than those living in the remote areas. Hence, iAgree can help to minimise the urban-rural digital divide associated with internet access and online learning experience.